A Smyrneika lexicon - Galdies, George. (Piscataway, NJ)
xxiii, 211 sayfa, [1] sayfa resim
Keywords: “A lexicon of Smyrneika, the Greek dialect that functioned as a lingua franca amongst the Levantine merchant communities of the Mediterranean. Rediscovering Turkey’s Ottoman past, including lost minority cultures… a study by three amateur lexicographers. The vocabulary is followed by a collection of proverbs and a series of dialogues illustrating the language and customs … “ -- Peter Mackridge www.oxford.academia.edu/PeterMackridge.